Collaborative Governance in the Development of Polman Bandung Campus II: Analysis of Transparency and Ethics in the Decision-Making Process - Aulia Rahman, Haikal; Myrna, Rita; Widianingsih, Ida; Hartoyo, Djoko (Indonesian Association for Public Administration (IAPA), 2024)
The development of Campus II of the Bandung Manufacturing Polytechnic (Polman) in Majalengka Regency is part of the development of the Rebana Metropolitan Area which aims to improve the quality of human resources (HR) through vocational education. This study aims to analyze the collaborative governance process applied in the development of the campus, with a focus on transparency and ethics in decision-making. The research method is qualitative descriptive, with data obtained through in-depth interviews and document analysis. The study results indicate that transparency is important in ensuring that every actor has equal access to information, which encourages active participation from all parties. Ethics in decision-making is also a major factor in maintaining the integrity of the collaboration process, which ensures that decisions taken consider the long-term interests of the community and industry in the Rebana Area. Cross-sector collaboration supported by transparency and ethics has proven effective in creating vocational education that is relevant to industry needs and can have a positive impact on regional economic growth. This study suggests increasing transparency and ethics in cross-sector collaboration to ensure the sustainability of similar projects in the future.